Kepatuhan Implementasi UNSCR 1325 oleh Korea Selatan Sebagai Upaya Memulihkan Kehormatan Korban Comfort Woman Sekaligus Peningkatan Partisipasi Perempuan dalam Isu Reunifikasi - Velia Rahmi (Journal of International Relations, 2023)
South Korea is a country that has experienced a period of conflict related to war crimes against women. During the Japanese occupation, many South Korean women were victims of the Japanese sexual policy system, known as comfort women. Meanwhile the South Korean government, which had experienced the problems of the civil war that occurred on the Korean peninsula, also had a bad impact on its women. Departing from these problems, the South Korean government decided to adopt UNSCR 1325 and formulate a RAN for its implementation in 2014. UNSCR 1325 is a resolution from the UN Security Council which regulates efforts to increase women's involvement in recovery as well as efforts to protect women in conflict situations. In line with the views of liberal feminism, UNSCR 1325 exists as an international media in bridging women so that they can act together with men in helping to achieve peace. The focus of this research is the implementation of UNSCR 1325 in the second period of South Korea's NAP for 2018-2020. The purpose of this study is to explain how South Korea implemented UNSCR 1325 in helping women, peace and security issues in their country. This researcher will use the compliance theory by Ronald B. Mitchell by using the Public Policy Trichotomy (Output, Outcomes, Impact) to analyze the implementation of UNSCR 1325 by South Korea into its country's NAP, especially for the second period of NAP 2018-2020. This study illustrates that the implementation of UNSCR 1325 for the second period of NAP by South Korea is still ongoing until the results are compiled and has not shown a significant impact. This is partly due to the limited resources in implementing the implementation of this resolution in South Korea.